2005
DOI: 10.1097/01.hjh.0000183524.73746.1b
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cell senescence is accelerated in both experimental hypertensive rats and patients with essential hypertension

Abstract: EPC senescence is accelerated in both experimental hypertensive rats and patients with essential hypertension, which may be related to telomerase inactivation. The hypertension-induced EPC senescence may affect the process of vascular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
138
1
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(148 citation statements)
references
References 27 publications
3
138
1
6
Order By: Relevance
“…The elevated HO-1 gene expression found in BS/GS patients and the increased levels of EPC observed in this study are consistent with the reports in an animal study that elevating HO-1 increased the numbers of circulating EPCs and bone marrow early and late outgrowth progenitor cells, and enhanced the maturation of bonemarrow-derived progenitor cells. 12 Moreover, these findings in BS/GS patients are the opposite of those found in hypertensive patients, who have reduced EPCs number, 3,38 increased oxidative stress 42 and altered FMD. 39 Furthermore, the increased number of EPC in BS/GS patients further strengthens the role of Ang II type 1 receptor signaling in EPC biology as BS/GS patients have blunted Ang II type 1 receptor signaling.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The elevated HO-1 gene expression found in BS/GS patients and the increased levels of EPC observed in this study are consistent with the reports in an animal study that elevating HO-1 increased the numbers of circulating EPCs and bone marrow early and late outgrowth progenitor cells, and enhanced the maturation of bonemarrow-derived progenitor cells. 12 Moreover, these findings in BS/GS patients are the opposite of those found in hypertensive patients, who have reduced EPCs number, 3,38 increased oxidative stress 42 and altered FMD. 39 Furthermore, the increased number of EPC in BS/GS patients further strengthens the role of Ang II type 1 receptor signaling in EPC biology as BS/GS patients have blunted Ang II type 1 receptor signaling.…”
Section: Discussionmentioning
confidence: 91%
“…The correlations noted are likely the result of previously reported relationships between endothelial function and EPC numbers, and function 35,36 along with the relationship between endothelial number and FMD. 37 All of these are altered in hypertension, 3,38,39 and in these alterations oxidative stress has a pivotal role. 40 Relationships between EPCs, FMD and HO-1 LA Calò et al in BS/GS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that senescence may serve as an important mechanism mediating EPC dysfunction. Decreased numbers and increased proportion of senescent EPC has been reported in patients with preeclampsia (34) or hypertension (35). Angiotensin II can induce EPC senescence through the induction of oxidative stress and influence telomerase activity (36).…”
Section: Senescence Of Endothelial Progenitor Cells (Epc)mentioning
confidence: 99%
“…This cell population, endothelial progenitor cells (EPCs), appears to be involved in both the maintenance of vascular integrity 14 and postnatal vasculogenesis (for example, tumor vascularization). [15][16][17][18] Since their identification by Asahara et al, 19 several studies have shown reduced numbers and/or impaired function of EPCs in a variety of cardiovascular risk states, including diabetes mellitus, 20 hypercholesterolemia, 21 hypertension, 22 chronic renal failure, 23 rheumatoid arthritis 24 and cigarette smoking. 25 Alternatively, cardiovascular protective factors such as exercise training, 26 statin therapy, 27 angiotensin II receptor antagonists 28 and peroxisome proliferatoractivated receptor agonists 29 are known to increase EPC number and function.…”
Section: Introductionmentioning
confidence: 99%